Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1177/000456329303000108
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium, Parathyroid Hormone, and Vitamin D Status in Children and Young Adults with Sickle Cell Disease

Abstract: SUMMARY. The concentrations of serum calcium, parathyroid hormone (PTH), 25 Hydroxyvitamin D (250HD), and 1,25 Dihydroxyvitamin D (1,25(OH}zD) were determined in 99 Saudi patients with sickle cell disease and in 104 matching healthy controls. Serum calcium and 250HD were significantly lower in the patients, with 140/0 and 12% of them had serum calcium and 250HD concentrations, respectively, below the normal range. PTH was significantly higher in the patients, with 31% having values above the normal range. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 22 publications
5
30
2
Order By: Relevance
“…These results are in line with those of previous studies on prevalence of vitamin D deficiency among SCA patients which was mentioned in the literature review [19]. Anyhow, previous reports on vitamin D levels in normal population of KSA, indicated that the majority of Saudis have low vitamin D levels mostly due to low dietary intake and sunlight avoidance [26]. In this study we did not detect any relationship between presence of AVN with vitamin D and calcium levels.…”
Section: Discussion:-supporting
confidence: 93%
See 1 more Smart Citation
“…These results are in line with those of previous studies on prevalence of vitamin D deficiency among SCA patients which was mentioned in the literature review [19]. Anyhow, previous reports on vitamin D levels in normal population of KSA, indicated that the majority of Saudis have low vitamin D levels mostly due to low dietary intake and sunlight avoidance [26]. In this study we did not detect any relationship between presence of AVN with vitamin D and calcium levels.…”
Section: Discussion:-supporting
confidence: 93%
“…While 13.4% of SCA patients have low serum calcium levels. These results match those observed in earlier studies on SCA patients in KSA and USA [26,27]. A possible explanation for this might be that SCA patients have hypocalcemia tendency due to multiple factors like poor intestinal absorption of calcium and vitamin D, which stimulate PTH secretion that might contribute to the skeletal changes seen in SCA patients [26].…”
Section: Discussion:-supporting
confidence: 90%
“…The mean serum phosphate value was 4.3 mg/dl in young sicklers and 5.3 mg/dl in normal controls. This finding could be explained by a finding of a previous study from this area that showed young sicklers to have higher than normal levels of parathyroid hormone which is expected to lower phosphate reabsorption by the renal tubules [3]. This led us to suspect that young sicklers may have a low renal tubular threshold for phosphate reabsorption.…”
Section: Discussionmentioning
confidence: 93%
“…These changes could be the result of repeated infarctions from sickling or disturbance in calcium and/or phosphate secondary to sickle cell nephropathy, in association with parathyroid gland abnormalities [1][2][3]. Tubular reabsorption of phosphate in sickle cell patients has been looked at in a small number of adult patients [4] but, to the best of our knowledge, not in children.…”
Section: Introductionmentioning
confidence: 99%
“…Both low 25(OH)D and bone mineral density (BMD) have been described in children with SCD [12][13][14]. While the pathophysiology of this observation is incompletely understood, it might be related to inadequate dietary intake, hemolysis, inflammation, limited cutaneous production of vitamin D 3 , and perhaps because of frequent hospitalization during the course of illness.…”
Section: Introductionmentioning
confidence: 99%